2020
DOI: 10.1002/jmv.26362
|View full text |Cite
|
Sign up to set email alerts
|

More than just a common cold: Endemic coronaviruses OC43, HKU1, NL63, and 229E associated with severe acute respiratory infection and fatality cases among healthy adults

Abstract: Respiratory viral infection can cause severe disease and hospitalization, especially among children, the elderly, and patients with comorbidities. In Brazil, the official surveillance system of severe acute respiratory infection (SARI) investigates influenza A (IAV) and B (IBV) viruses, respiratory syncytial virus (RSV), adenovirus (HAdV), and parainfluenza viruses (hPIV 1-3). In Rio Grande do Sul (RS), Brazil, many fatalities associated with SARI between 2013 and 2017 occurred among patients without underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…IFR will depend on settings and populations involved. For example, even ‘common cold’ coronaviruses have IFR~10% in nursing home outbreaks 79 …”
Section: Discussionmentioning
confidence: 99%
“…IFR will depend on settings and populations involved. For example, even ‘common cold’ coronaviruses have IFR~10% in nursing home outbreaks 79 …”
Section: Discussionmentioning
confidence: 99%
“…The highly transmissible human pathogen IAV mainly attacks human respiratory epithelium with its hemagglutinin binding with sialic acid to initiate endocytosis [18]. Severe symptoms after IAV infection are commonly found in the infant, elderly, pregnant, as well as the immunocompromised populations [19][20][21][22]. IAV can cause serious pandemics in a short time, with shocking and heart-wrenching facts in history, e.g., the 1918 Great Influenza killed almost 1/30 of the global population only in 1.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID‐19) caused by the severe acute respiratory syndrome coronavirus 2 is now being a disaster, as of November 3, 2020, the World Health Organization have reported 46 million cases and 1.2 million deaths globally 1 . Studies have reported that respiratory infectious diseases such as influenza, varicella, herpes zoster, rubella, and measles are suppressed during the fight against the pandemic of COVID‐19, 2–4 and the respiratory infection 5 . However, while schools in Guangzhou have been reopened, we have monitored several outbreaks of unknown fever, and later proved to be human rhinovirus (HRV) infections.…”
Section: Characteristics School a School B School C School D School Ementioning
confidence: 99%